Adaptation of the STEM Value-Expectancy Assessment Scale to Turkish Culture - Yakup Özkan Ozkan; Ilbilge Dokme; Arif Acıksoz (International Journal of Assessment Tools in Education)
This study aimed to obtain a measurement tool in Turkish culture to determine the motivation of university students (pre-service teachers) toward STEM based on the expectancy-value theory. For this purpose, the validity and reliability studies of the Turkish version of the STEM Value-Expectancy Assessment Scale developed by Appianing and Van Eck (2018) were conducted. A confirmatory factor analysis (CFA) was undertaken to check the validity of the scale administered to 196 pre-service science teachers selected by purposeful sampling and Cronbach’s alpha internal consistency coefficients were examined for the reliability evaluation. One item that showed a tendency to be loaded on two factors in CFA was removed and the repeated CFA confirmed a good fit for the two-factor structure as in the original scale. In the reliability analysis, the internal consistency coefficients were calculated as .87 for the whole scale, .82 for the perceived value component, and .82 for the expectations of success in STEM careers component. When the validity and reliability results were evaluated together, it was concluded that the adaptation of the scale to Turkish culture was a measurement tool that has high validity and reliability that could be administered to prospective teachers.